A multicentre survey of paediatric out-of-hospital cardiac arrest incidence, aetiology, and survival in New South Wales over an 11-year period. (4th February 2022) - Youssef, D; Singh, A; Ayer, J; Turner, C; Christoff, A; Bromage, J; Balit, C; Numa, A; Skinner, J R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Out-of-hospital cardiac arrest (OOHCA) is commonly associated with pulseless ventricular tachycardia and ventricular fibrillation (VT/VF) and cardiac aetiologies. One New South Wales (NSW) ambulance registry reported(1) cardiac aetiologies with a prevalence of 31% among OOHCA cases. Multicentre OOHCA data and NSW's well-developed services for cardiac genetic predisposition screening motivate us to consider the following study of paediatric OOHCA in this state. Purpose: We present a multicentre, retrospective study summarizing the demographics, clinical characteristics, incidence, presenting rhythm, and survival-to-discharge status of paediatric OOHCA cases in NSW over an 11-year period. We also present and categorize diagnostic outcomes for patients presenting with VT/VF. Methods: A retrospective case series of 298 patients admitted to one of three NSW PICUs (two in Sydney and one in Newcastle) under 18 years of age and presenting with OOHCA between January 2009 and December 2019. Results: Out of 296 paediatric OOHCA patients that survived until PICU admission, 187 (63.2%) were male and 160 (54.1%) survived until hospital discharge. Of those surviving to discharge, 105 (65.6%) were male. Presenting rhythm was asystole or pulseless electrical activity in 240 patients (84.8%, aged 0–17 years, median age 2 years), VT/VF in 41 patients (14.5%, aged 0–16 years, median age 9 years), and complete heart block in 2 patients (0.7%, aged 4–4 years, median age 4 years). Survival was higher in the VT/VF group (82.9%) relative to the asystole and pulseless electrical activity group (50.0%). Of the 41 patients presenting with VT/VF, 13 (31.7%) had a predisposing cardiac condition (2 truncus arteriosus, 1 arrhythmogenic right ventricular cardiomyopathy, 1 double outlet right ventricle, 1 hypoplastic right ventricle, 1 left ventricular non-compaction, 2 asystolic syncope, 2 left ventricular intramyocardial fibroma, 1 familial dilated cardiomyopathy, and 2 undetermined cardiac conditions) and 20 (48.8%) had a genetic condition (9 catecholaminergic polymorphic ventricular tachycardia, 4 hypertrophic cardiomyopathies, 1 Nkx-2.5 mutation, 2 Long QT syndrome, 2 PPA2 mutation, 1 TANGO2 mutation, 1 supraventricular tachycardia). Toxins or trauma were involved in 4 (9.8%) cases, while no cause was determined in 4 (9.8%) other cases. Conclusions: Overall, 54.1% of paediatric OOHCA patients admitted to PICU survived until hospital discharge, rising to 82.9% among those with VT/VF. Genetic conditions (48.8%), predominated by CPVT, were present in over one-third of VT/VF cases: this figure confirms the continued need for detailed cardiac/genetic assessment for paediatric OOHCA cases.